Answers

2016-04-14T15:31:04+05:30
Given ,
quadratic polynomial = 4s²- 4s +1= q(y)
to find the zeroes of the given quadratic polynomial,
q(y) = 0
4s² - 4s+1 = 0
⇒4s²-2s-2s+1 = 0
⇒2s(2s-1)-1(2s-1) = 0
⇒(2s-1) (2s-1) = 0
⇒2s - 1  = 0 ; 2s - 1= 0
⇒s = 1/2, 1/2
therefore, the zeroes of the polynomial = 1/2,1/2
now,
sum of the zeroes = 1/2 + 1/2 = 2/2 = -(co-efficient of s)
                                                              (co-efficient of s²)
product of the zeroes = 1/2(1/2) = 1/4 = constant term / coefficient of s²
1 5 1